Probiotics in the prevention of antibiotic-associated diarrhoea and Clostridium difficile infection - Hickson, Mary (SAGE Publications, 2011)
Diarrhoea, as a common side effect of antibiotics, increases treatment costs and length of stay in acute healthcare facilities. One potential strategy to prevent this side effect is the concurrent use of probiotic bacteria or yeast. This review discusses the evidence for the efficacy of probiotics in the prevention of antibiotic-associated diarrhoea and Clostridium difficile infection; the potential mechanisms by which probiotics may work; their safety; what future research is required; and recommendations for use in clinical practice.